2018
DOI: 10.12775/cjfa.2017.019
|View full text |Cite
|
Sign up to set email alerts
|

Non-Financial Information and Integrated Reporting in the Hospitality Industry: Case Study of Croatia

Abstract: Keywords:Directive 2014/95/EU, non-financial information, sustainability, integrated reporting, hospitality industry, Croatia. J E L Classification: M41, M48, Q56, D81.Abstract: Subsequent to the Directive 2014/95/EU (EUDNFI) and Croatian Accounting Act (CAA), available non-financial information disclosed by Croatian hospitality companies in non-financial (sustainability) reports were analysed for their breadth and quality using the content analysis method The results of preliminary research of hospitality ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…or companies that belong to critical industrial sectors (e.g., mining and oil companies) [35][36][37]. In addition, before the inclusion of the EU Directive, several studies were conducted on the non-financial reporting of the hospitality industry, the results of which showed that their quality was not satisfactory [38][39][40][41][42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…or companies that belong to critical industrial sectors (e.g., mining and oil companies) [35][36][37]. In addition, before the inclusion of the EU Directive, several studies were conducted on the non-financial reporting of the hospitality industry, the results of which showed that their quality was not satisfactory [38][39][40][41][42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…From a wider perspective, Peršić and Halmi (2017) attempted to explore the specifics of non-financial information and integrated reporting in the Croatian hospitality sector and uncovered very few companies disclosing non-financial information within their annual reports, or of a satisfactory quality to satisfy national regulations. Meanwhile, the progress from stand-alone CSR to integrated reporting was also examined by Rupley et al (2017) through an analysis of the reports from eight front-running US companies, finding that, overall, current integrated reports do not provide the information most highly rated by investors.…”
Section: Literature Reviewmentioning
confidence: 99%